COMPARATIVE STUDY OF SLA: EFFECTS OF EARLY EXPOSURE, EDUCATION, AND PSYCHOLOGY ON SIXTH-GRADERS (TAMADDUN NURI JURNALI, 2024)
This study compares the SLA experiences of two sixth-grade pupils with differing linguistic abilities, highlighting the impact of early exposure, teaching methods, and emotional factors. Using Krashen’s and Vygotsky’s theories, it underscores the importance of tailored strategies, and emotional support in fostering effective language acquisition and learner confidence.